Lamin B receptor upregulation in metastatic melanoma causes nuclear envelope fragility in confined migration during cancer invasion - Michelle A. Baird; Cayla E. Jewett; Daniela A. Malide; Lisa Kratz; Alexander X. Cartagena-Rivera; Robert S. Fischer; Clare M. Waterman (Proceedings of the National Academy of Sciences, 2026)
Cancer cells migrate through regions of tissue confinement during metastasis, causing nuclear envelope (NE) rupture, which generates heritable DNA damage and disease aggression. We sought to determine if NE rupture was intrinsic to malignant transformation and seek a mechanistic cause. We found that metastatic cells from multiple cancer subtypes have increased NE fragility in confinement compared to their benign counterparts. Meta-analysis of transcriptomic data from clinical samples of melanoma progression together with an siRNA-based live-cell confinement screen revealed that lamin B receptor (LBR) transcriptional upregulation correlates with melanoma progression and NE fragility. LBR is an inner nuclear membrane protein (INM) that scaffolds lamins and chromatin and has sterol reductase activity in the cholesterol biosynthesis pathway. Applying superresolution and atomic force microscopies to characterize the cellular and biophysical events leading to NE rupture revealed that upregulated LBR increased nuclear deformability and can generate local ruptures of the INM, promoting blebs in the nuclear membrane that burst to release nuclear contents into the cytoplasm. Structure–function analysis showed that LBR’s sterol reductase activity is required for its promotion of NE fragility in cells confined in vitro. Use of tumor organoids and an in vivo melanoma model revealed that upregulation of LBR was associated with increased NE fragility, metastatic invasion, and decreased patient survival. Thus, upregulation of LBR in melanoma promotes nuclear deformability, while LBR’s sterol reductase activity causes fragility and instability of the nuclear membrane, and these changes in the nucleus provide a possible mechanism for increased genetic heterogeneity in melanomas.